Comparison of two different suction curettage methods in cesarean scar pregnancy treatment - Burak Elmas; Neslihan Ozturk; Emine Kizil; Bergen Laleli Koc; Ugurcan Zorlu; Duygu Tugrul Ersak; Turkan Dikici Aktas; Asuman Erten; Salim Erkaya (BMC Pregnancy and Childbirth)
Abstract Background Cesarean scar pregnancy (CSP), the incidence of which is increasing, can lead to life-threatening consequences. In this study, it was aimed to compare the results of two different ultrasound-assisted suction curettage (SC) approaches that we applied to endogenous type CSPs in different time periods. Methods Patients who were diagnosed with CSP and treated with SC in the early pregnancy service between January 2012 and March 2019 were included in the study. While classical SC was applied until December 2016, patients were treated with SC modified by us after this date. Demographic characteristics, preoperative clinical findings, intraoperative characteristics and postoperative short-term follow-up of these two groups of patients belonging to different time periods were compared. Results 34 patients were treated with classic SC (Group 1) and 32 patients with modified SC (Group 2). The amount of decrease in Hemoglobin values measured at the sixth hour postoperatively compared to the preoperative period was found to be less in group 2 (1.01 ± 0.67 g/dl) than in group 1 (1.39 ± 0.85 g/dl) (p = 0.042). The treatment failure rate was found to be lower in group 2 (p = 0.028). According to the results of multiple logistic regression analysis of significant factors associated with treatment outcome, myometrial thickness measurement and the largest gestational diameter measurement were found to be significant independent factors. Conclusion In CSP cases, SC procedure with abdominal ultrasonography is an effective and reliable approach. At the beginning of this surgical procedure, if the gestational sac is removed from the uterine wall with the curettage cannula before suction, the success of the procedure will increase even more.